PENINGKATAN STATUS GIZI ANAK BALITA DI LINGKUNGAN KELUARGA PEKERJA WANITA - M. Saidin; Sukati Sukati; Sri Muljati (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 1998)
A study of nutritional improvement in children under five years old of working women families was conducted in the subdistrict of Kali Wungu, district of Kudus, Central Java. A total of 83 preschool children (19-55 months old) with mild under nutrition was divided into two groups. The first was intervention group received food supplement containing 300 kcal of energy and 5 g of protein, three times a week for the duration of 14 weeks. The second was control group, did not receive any food supplement. Baseline data collection included identity, body weight and height, haemoglobine, haematocrit, serum ferritin, food consumption of the children and socioeconomic status of the household and was conducted in both groups before starting with the supplementary feeding. Just after baseline data collection, both groups received deworming (combantrin syrup). Multivitamins were given every day for tire first ten days and another ten days in the middle of the intervention. While iron pill (Ferro sulphate) 30 mg was given weekly. The evaluation were conducted after 1-1 weeks of intervention. The results of the study revealed that: 1) the energy intake of daily food consumption of both groups of children was lower than Recomended Dietary Allowances (61% RDA),· 2) the average energy intake originating from the portion of the food supplement consumed was only 225 Kcal (75% of the total energy provided); 3) supplementary feeding three times per week for 14 weeks together with providing a medicine package consisting of deworming (combantrin), multivitamins (provit) and iron pill increases nutritional status based on weight for age by 2.7%; 4) supplementary feeding three times per week for 14 weeks together with medicine package raises Hb levels 0.61 g/dl; 5) the medicine package only, without supplementary feeding increases Hb levels 0.21 g/dl (control group); 6) supplementary feeding activities for children of working women families could be managed by caders as volunteers under supervision of the village's midwive. Keywords: food supplement, nutritional improvement, working women families